High efficiency red emission carbon dots based on phenylene diisocyanate for trichromatic white and red LEDs. Issue 36 (3rd September 2018) - Han, Zhixia; Wang, Kai; Du, Fanglin; Yin, Zhengmao; Xie, Zheng; Zhou, Shuyun
Abstract : Recently, carbon dots have emerged as novel luminous materials due to their excellent luminous performance. Abstract : Recently, carbon dots have emerged as novel luminous materials due to their excellent luminous performance. However, it is still challenging to obtain high quantum yields of red emission in carbon dots. Herein, we synthesized a new type of high efficiency red emission-carbon dots from 1, 4-phenylene diisocyanate by a solvothermal method. Furthermore, the carbon dots were used to fabricate trichromatic white LEDs that possess a high luminous efficacy and color rendering index. In this study, we propose an approach for achieving high carbon dots with quantum yields by introducing more conjugated nitrogen groups in a graphitic layered structure. Moreover, the high efficiency red emission carbon dots can greatly promote carbon dots' application in white LEDs, demonstrating that the as-prepared carbon dots are promising materials in LEDs, displays and even in other light applications.